Method for preparing porous metal fiber mat
The preparation of porous metal fiber mats by electrospinning and heating solves the problem of low specific surface area of existing materials, achieves the combination of high specific surface area and mechanical strength, and improves its application performance in the fields of catalysis and battery.
Patent Information
- Application Number
- CN202380055970.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-25
- Filing Date
- 2023-07-25
- Publication Date
- 2025-03-11
AI Technical Summary
The specific surface area of existing porous metal materials is relatively low, which limits its application performance in the fields of catalysis, lithium-ion batteries, etc.
Porous metal fiber mats are prepared by electrospinning method, electrospinning is performed by providing a slurry containing metal particles and a polymer carrier, followed by heating to produce a porous metal fiber mat with a high specific surface area.
The high specific surface area and mechanical strength of porous metal fiber mats are achieved, and its application performance in catalysis, batteries and other fields is improved.
Smart Images

Figure CN119604639A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to porous metal materials which can be used in the fields of electrochemistry and catalysis. Background Art
[0002] Porous metal materials are a particularly useful class of materials in the fields of catalysis and energy. An example of such a material is metal foam. However, conventional methods for producing metal foams produce porous metals with low specific surface areas (<500 cm -1 ) materials. Such metal foams have limited utility in fields such as catalysis, lithium-ion batteries, supercapacitors, etc., where the performance of the material is proportional to its specific surface area. US2021 / 344017 A and CN107552797 A each disclose a metal foam prepared by freeze casting.
[0003] Therefore, there is a need to develop porous metal materials with high specific surface area but maintaining mechanical strength. The present invention uses an electrospinning-based method to meet this need. Summary of the invention
[0004] In a first aspect, there is provided a method for preparing a porous metal fiber mat, the method comprising:
[0005] a. providing a slurry, the slurry comprising particles in a solvent and a polymer carrier, the particles being selected from metal particles, metal compound particles or a combination thereof;
[0006] b. electrospinning the slurry to produce a composite fiber mat; and
[0007] c. Heating the composite fiber mat to produce a porous metal fiber mat.
[0008] In a second aspect, a porous metal fiber mat is provided, which can be obtained by the method according to the first aspect.
[0009] In a third aspect, there is provided a porous metal fiber mat, wherein the metal fiber mat has:
[0010] At least 500cm -1 The specific surface area of
[0011] At least 0.05mm thickness.
[0012] In a fourth aspect, provided herein is a use of the porous metal fiber mat according to the second aspect or the third aspect as an electrode.
[0013] In a fifth aspect, provided herein is a use of the porous metal fiber mat according to the second aspect or the third aspect as a catalyst or catalyst support.
[0014] In a sixth aspect, provided herein is a use of the porous metal fiber mat according to the second aspect or the third aspect as a filter material. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 SEM images of nickel foam (Ni-5763, obtained from Recemat BV) and SEM images of a nickel fiber mat according to the present invention were compared.
[0016] Figure 2 The tensile strength test results of the nickel fiber mat and nickel foam according to the present invention obtained in Example 7 are shown.
[0017] Figure 3 Compression test results of the nickel fiber mat and nickel foam according to the present invention obtained in Example 7 are shown.
[0018] Figure 4 Shown are electrochemical characteristics observed in Example 8 when the nickel fiber mat according to the present invention and the nickel foam were each used as an electrochemical catalyst for the polysulfide oxidation / reduction reaction.
[0019] Figure 5 The electrochemical characteristics observed when using the nickel fiber mat according to the present invention as a cathode of a lithium ion battery are shown.
[0020] Figure 6 The electrochemical characteristics observed when the nickel fiber mat according to the present invention is used as two electrodes of an alkaline water electrolyzer are shown. DETAILED DESCRIPTION
[0021] Method for preparing porous metal fiber mat
[0022] In a first aspect, there is provided a method for preparing a porous metal fiber mat, the method comprising:
[0023] a. providing a slurry, the slurry comprising particles in a solvent and a polymer carrier, the particles being selected from metal particles, metal compound particles or a combination thereof;
[0024] b. electrospinning the slurry to produce a composite fiber mat; and
[0025] c. Heating the composite mat to produce a porous metal fiber mat.
[0026] The porous metal fiber mat obtainable by this method contains a plurality of metal fibers. The metal fibers have a high aspect ratio such that their length is at least one order of magnitude greater than their diameter. The method according to the first aspect produces a porous metal fiber mat, wherein the plurality of metal fibers are arranged to provide a porous material having a high specific surface area.
[0027] The first step (step a) of the method involves providing a slurry comprising particles selected from metal particles, metal compound particles, or a combination thereof in a solvent and a polymer carrier.
[0028] The particles in the slurry are selected from metal particles, metal compound particles or a combination thereof. Metal particles are particles containing metal atoms in a zero valence state.
[0029] The metal particles may be nickel particles, copper particles, iron particles, aluminum particles, titanium particles, zinc particles or a mixture thereof. Preferably, the metal particles may be zinc particles, aluminum particles or a mixture thereof.
[0030] The metal compound particles are particles containing compounds containing metal cations. The metal compound particles can be metal oxide particles, metal sulfide particles, metal carbide particles, metal nitride particles, metal phosphide particles, metal carbonate particles or a combination thereof. The metal compound particles can be nickel compound particles, copper compound particles, iron compound particles, aluminum compound particles, titanium compound particles, zinc compound particles or a mixture thereof.
[0031] Preferably, the metal compound particles may be nickel compound particles, copper compound particles, iron compound particles, zinc compound particles or a mixture thereof. More preferably, the metal compound particles may be nickel compound particles, copper compound particles or a mixture thereof.
[0032] The metal compound particles may be metal oxide particles. The metal oxide particles are particles containing a compound containing metal cations and oxygen anions. The metal oxide particles may be nickel oxide particles, copper oxide particles, iron oxide particles, aluminum oxide particles, titanium oxide particles, zinc oxide particles, or a mixture thereof.
[0033] Preferably, the metal oxide particles may be nickel oxide particles, copper oxide particles, iron oxide particles, zinc oxide particles or a mixture thereof. More preferably, the metal oxide particles may be nickel oxide particles, copper oxide particles or a mixture thereof.
[0034] The slurry may include a sintering aid. If present, the sintering aid may preferably be present in an amount of about 1 wt. % to about 15 wt. % based on the amount of the metal particles, metal compound particles, or a combination thereof.
[0035] In the case where the metal particles are aluminum particles, the sintering aid may preferably be selected from copper, tin, zinc, magnesium, KAlF 4 、AlCl 3 NH 4 Cl, LiCl or a mixture thereof. Preferably, the sintering aid is magnesium and / or KAlF 4More preferably, the sintering aid is magnesium or magnesium and KAlF 4 mixture.
[0036] In case the metal particles are titanium particles, the sintering aid may preferably be iron, magnesium, copper, zinc, nickel, silicon or a mixture thereof.
[0037] The average size of the particles can be 0.01 μm to 2 μm. The average size of the particles can be 0.1 μm to 2 μm, for example 0.2 μm to 0.8 μm. Therefore, the average size of the particles can be about 0.5 μm. In this case, the average size is the numerical average diameter of the particles. In this case, the diameter of the particles is the longest straight-line distance between the two edges of the particles. The average particle size can be determined by obtaining a microscope image (e.g., a scanning electron microscope (SEM) image) of a particle sample and measuring the size of the particles in the microscope image and calculating the average value. For example, the average particle size can be determined by obtaining SEM images of three different observation positions of the sample, measuring the size of 20 randomly selected particles in each SEM image, and then calculating the average particle size.
[0038] The particle loading in the slurry, i.e., the concentration of metal particles and / or metal oxide particles in the slurry, can be between 0.2 g mL -1 Up to 0.9 g mL -1 For example, the particle loading in the slurry can be about 0.5 g mL -1 .
[0039] In slurry, provide polymer carrier, so that it can be electrostatically spun.Therefore, polymer carrier can be any polymer that can be electrostatically spun.Therefore, polymer carrier can be polyacrylonitrile (PAN), polyethylene oxide (PEO), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polyamide (nylon), polymethyl methacrylate (PMMA), polyvinyl ether (PVE), polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), chitosan, lignin, cellulose or polylactic acid (PLA).For example, polymer carrier can be polyacrylonitrile (PAN), polyethylene oxide (PEO), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polyamide (nylon), polymethyl methacrylate (PMMA) or polyvinyl ether (PVE).
[0040] The weight average molecular weight of the polymer carrier can be 10 kg mol -1 Up to 1500 kg mol -1 For example, the weight average molecular weight of the polymer carrier can be in the range of 15 kg mol -1 Up to 1300 kg mol -1The weight average molecular weight of the polymer carrier can vary depending on the type of polymer used. For example, the polymer carrier can be a polymer with a weight average molecular weight of 50 kg mol -1 Up to 400 kg mol -1 (e.g. 200 kg mol -1 Up to 260 kg mol -1 (e.g., about 230 kg mol -1 The polymer carrier may be a PAN having a weight average molecular weight of 15 kg mol -1 Up to 500 kg mol -1 (e.g. 15 kg mol -1 Up to 60 kg mol -1 (e.g., about 30 kg mol -1 )) of PEO, or a weight average molecular weight of 30 kg mol -1 Up to 90 kg mol -1 (For example, about 60 kgmol -1 ) or PEO with a weight average molecular weight of 70 kg mol -1 Up to 130 kg mol -1 (e.g., about 100 kg mol -1 The polymer carrier may be a PEO having a weight average molecular weight of 50 kg mol -1 Up to 1300 kg mol -1 PVP.
[0041] The amount of polymer carrier provided in the slurry may vary depending on the type of polymer and its weight average molecular weight. For example, in the case where the polymer carrier is 200 kg mol -1 Up to 260 kg mol -1 (e.g., about 230 kg mol -1 ) of PAN, it can be used at 0.05 g mL -1 Up to 0.15 g mL -1 Alternatively, the polymer carrier is a polymer having a molecular weight of 15 kg mol -1 Up to 60 kg mol -1 (e.g., about 30 kg mol -1 ) of PEO, it can be used at 0.08 g mL -1 Up to 0.20 g mL -1 Alternatively, the polymer carrier is a polymer having a molecular weight of 30 kg mol -1 Up to 90kgmol -1 (e.g., about 60 kg mol-1 ) of PEO, it can be used at 0.04 g mL -1 Up to 0.15 g mL -1 Alternatively, the polymer carrier is a polymer having a molecular weight of 70 kg mol -1 Up to 130 kg mol -1 (e.g., 100 kg mol -1 ) of PEO, it can be used at 0.02g mL -1 Up to 0.08 g mL -1 The amount is provided in the slurry.
[0042] The solvent in the slurry can be any solvent that can be used for electrospinning. For example, the solvent can be water, dimethylformamide (DMF), ethanol, acetone, acetic acid, formic acid, chloroform, dichloromethane (DCM), dimethyl sulfoxide (DMSO), dimethylacetamide (DMA), toluene, oxolane or a mixture thereof. For example, the solvent can be water or DMF.
[0043] The slurry provided in the first step (step a) can be prepared by mixing the particles, polymer carrier and solvent together at an elevated temperature, as long as the temperature is below the boiling point of the solvent and is not a temperature that would cause the polymer carrier to decompose. In this case, the elevated temperature is any temperature above room temperature (in this application, the temperature is considered to be a temperature in the range of 18°C to 25°C). For example, the slurry can be prepared by mixing the solvent, polymer carrier and particles at a temperature of at least 50°C. For example, the slurry can be prepared by mixing the solvent, polymer carrier and particles at a temperature of 50°C to 80°C.
[0044] The slurry may further comprise a surfactant. The surfactant may be incorporated into the slurry by mixing it with the solvent, polymer carrier and particles at an elevated temperature as described in the previous paragraph. The surfactant may be any surfactant that improves the miscibility of the components of the slurry. For example, the surfactant may be Triton X-100 (2-[4-(2,4,4-trimethylpentan-2-yl)phenoxy]ethanol), oleic acid, CTAB (hexadecyltrimethylammonium bromide), (CMC) carboxymethylcellulose or a combination thereof. The surfactant may be added at 0.001 g mL -1 Up to 0.05 g mL -1 The concentration of is provided in the slurry.
[0045] The weight ratio of the particles in the slurry to the polymer carrier can vary as long as the slurry remains electrospinnable. The weight ratio of the particles in the slurry to the polymer carrier can be at least 1: 1. For example, the weight ratio of the particles in the slurry to the polymer carrier can be 1: 1 to 50: 1, 1.5: 1 to 15: 1, or 15: 1 to 9: 1.
[0046] The second step (step b) of the method involves electrospinning the slurry to produce a composite fiber mat. The composite fiber mat is made from composite fibers of the electrospun slurry. Electrospinning is a well-known method of producing fibers in which a charged polymer solution is drawn through an electric field, wherein the produced fibers are collected in a collection plate.
[0047] Electrospinning can be performed with the slurry at room temperature or at elevated temperature (both temperatures are defined above). For example, electrospinning can be performed with the slurry at a temperature of 18°C to 80°C.
[0048] The electrospinning voltage (i.e., the voltage of the electric field applied during electrospinning) can be varied to affect the physical properties of the resulting composite fibers. For example, electrospinning can be performed at a voltage of 5 kV to 25 kV.
[0049] The electrospinning rate (i.e., the rate at which the slurry passes through the electric field) can be varied to affect the physical properties of the resulting composite fibers. For example, the electrospinning rate can be varied at 0.1 mL h -1 to 10 mL h -1 Electrospinning was performed at a rate of .
[0050] The slurry can be drawn through the electrospinning nozzle to spin the composite fiber, or the fiber can be spun without using a nozzle (i.e., in a nozzleless electrospinning process). When using an electrospinning nozzle, one electrospinning nozzle can be used, or multiple electrospinning nozzles can be used. The diameter of the electrospinning nozzle used in the electrospinning process can be varied to affect the physical properties of the composite fiber produced. For example, an electrospinning nozzle with a diameter of No. 15 to No. 25 (0.51 mm to 18.3 mm) can be used for electrospinning.
[0051] The distance between the electrospinning nozzle and the collection can be varied to affect the physical properties of the resulting composite fibers. For example, electrospinning can be performed using a collection plate located 2 cm to 30 cm from the electrospinning nozzle.
[0052] The relative humidity of the environment can affect the properties of the composite fibers produced during electrospinning. Relative humidity is the ratio of the partial pressure of water vapor in the air to the equilibrium vapor pressure of water. Electrospinning can be performed at a relative humidity of no more than 80%.
[0053] The third step of the method (step c; heating step) involves heating the composite fiber mat to produce a porous metal fiber mat. This may be referred to as calcining. This heating step removes the polymer carrier and sintering the particles in the composite fiber mat. During the heating step, the composite fiber mat may be heated to a temperature of 200° C. to 2000° C. For example, the composite fiber mat may be heated at a temperature of 400° C. to 1200° C.
[0054] The rate of temperature increase during the heating step can be controlled. For example, the temperature can be increased at 0.2°C min during the heating step. -1 to 2℃min -1 After the composite fiber mat is heated to the desired temperature, it is maintained at the temperature for a sufficient time to remove the polymer carrier from the composite fiber mat. For example, the composite mat can be heated at the desired temperature for at least 2 hours (e.g., about 5 hours).
[0055] The heating step may be performed in air, or may be performed in an inert atmosphere (eg, a nitrogen atmosphere).
[0056] When metal compound particles (e.g., metal oxide particles) are present in the composite fiber mat, the heating step reduces these particles in the composite fiber mat to produce a porous metal fiber mat. In this case, the heating step includes subjecting the composite fiber mat to conditions that reduce the metal compound particles in the composite mat. For example, the composite fiber mat may be exposed to H during the heating step. 2 Contact. 2 Can be used as a gas mixture (such as containing H 2 and N 2 The gas) is provided as part of the 2 It can be used as a 2 Therefore, H 2 It can be used with 5 vol% H 2 / N 2 (i.e., containing 5 vol% H 2 N 2 ) in the form of.
[0057] One option is to carry out the heating step in two stages: a first stage in which the polymer carrier in the composite fiber mat is removed and the particles are sintered as described above, and then a second stage in which the metal compound particles are reduced. These stages can be carried out in the same equipment (e.g., a furnace).
[0058] The second stage may include heating to a temperature of 200°C to 2000°C (e.g., a temperature of 400°C to 1200°C). The rate of temperature increase during this stage may be controlled. For example, the temperature may be increased at 0.2°C min during the second stage. -1 to 2℃min -1 The temperature is increased at a rate of 1:1. After reaching the desired temperature, the temperature is maintained for a sufficient time to reduce the metal compound and produce a porous metal fiber mat. For example, the composite fiber mat can be heated at the desired temperature for at least 2 hours (e.g., about 5 hours). 2 The second stage is carried out in the case of 2 Can be used as a gas mixture (such as containing H 2 and N 2 The gas) is provided as part of the 2 It can be used as a 2 Therefore, H 2 It can be used with 5 vol% H 2 / N 2 (i.e., containing 5 vol% H 2 N 2 ) in the form of.
[0059] The method can be used to prepare a porous metal fiber mat of increased thickness by folding the composite fiber mat onto itself prior to the third step. Alternatively, a plurality of composite fiber mats prepared according to the method (i.e. prepared according to the first and second steps) are stacked on top of each other prior to the heating step. The folded or stacked composite fiber mat can be subjected to a preheating step, prior to which the composite fiber mat is heated to sinter the folded / stacked portions of the mat together. For example, the preheating step can involve heating the folded / stacked composite fiber mat to a temperature of 120°C to 400°C (e.g., about 250°C) for a period of time (e.g., about 2 hours) prior to the heating step. The rate of temperature increase during the preheating step can be controlled. For example, the temperature can be increased at 0.2°C min during the preheating step. -1 to 2℃min -1 The rate at which the temperature increases.
[0060] Porous metal fiber mat
[0061] In a second aspect, a porous metal fiber mat is provided, which can be obtained by the method according to the first aspect.
[0062] In a third aspect, there is provided a porous metal fiber mat, wherein the metal fiber mat has:
[0063] At least 500cm -1 The specific surface area of
[0064] At least 0.05mm thickness.
[0065] A porous metal fiber mat contains a plurality of metal fibers. The metal fibers have a high aspect ratio, such that their length is many orders of magnitude greater than their diameter. A porous metal fiber mat is formed from a plurality of metal fibers arranged to provide a porous material having a high specific surface area.
[0066] The metal fibers in the porous metal fiber mat may be nickel fibers, copper fibers, iron fibers, aluminum fibers, titanium fibers or zinc fibers. The thickness of the porous metal fiber mat may be in the range of 0.05 mm to 10 mm.
[0067] The porosity of porous metal fiber can be at least 50vol%, for example, at least 70vol% or at least 80vol%. In this case, porosity is a measure of the void space in the mat (i.e., the space not occupied by the fiber in the mat) part. Therefore, the porosity of porous metal fiber mat can be 80vol% to 98vol%, for example, 80vol% to 90vol%. The porosity of porous metal fiber mat can be measured by simple analysis of the weight and volume of the mat or Brunauer-Emmett-Teller (BET) analysis. Porosity can also be determined using Tau-Factor software according to SJ Cooper et al., "Software X (SoftwareX)", 2016, 5, 203-210 (https: / / doi.org / 10.1016 / j.softx.2016.09.002) described in the method.
[0068] The specific surface area of the porous metal fiber mat, i.e. the total area surface area per unit mass of the mat, is at least 500 cm -1 Therefore, the specific surface area of the porous metal fiber mat can be 500cm -1 Up to 50000cm -1 The specific surface area of the porous metal fiber mat can be determined by Brunauer-Emmett-Teller (BET) analysis. The specific surface area can also be determined using Tau-Factor software according to the method described in SJ Cooper et al., Software X, 2016, 5, 203-210 (https: / / doi.org / 10.1016 / j.softx.2016.09.002).
[0069] The porous metal fiber mat contains a plurality of pores that allow access to the interior surface of the mat. The porous metal fiber mat may have pores with an average size in the range of 0.5 μm to 5.0 μm, for example, the average pore size may be about 2.5 μm. In this case, the average pore size is the numerical average size of the pores in the porous metal fiber mat, where the "pore size" is the farthest straight-line distance between the two edges of the pores. The average pore size can be determined by measuring the size of the pores in the porous metal fiber mat visible in a microscope image, such as a scanning electron microscope (SEM) image.
[0070] The thickness of the porous metal fiber mat is at least 0.05 mm. Thus, the thickness of the porous metal fiber mat may be in the range of 0.05 mm to 10 mm. In this case, the thickness defines the smallest dimension of the three spatial dimensions of the mat (i.e., the other two spatial dimensions of the mat, length and width, are greater than the thickness).
[0071] The porous metal fiber mat according to the third aspect can be obtained by the method according to the first aspect.
[0072] In a fourth aspect, the present invention provides the use of the porous metal fiber mat according to the second aspect or the third aspect as an electrode. For example, the porous metal fiber mat can be used as an electrode in a battery such as a lithium sulfur battery or a redox flow battery. The porous metal fiber mat can also be used as an electrode in a supercapacitor or an electrode in a fuel cell unit.
[0073] In a fifth aspect, the present invention provides the use of the porous metal fiber mat described in the second aspect or the third aspect as a catalyst or catalyst carrier. When the porous metal fiber mat is used as a catalyst, it provides a large active surface area (i.e., the mat is used as a heterogeneous catalyst) that can be used to catalyze reactions occurring in the liquid phase or gas phase. The high porosity of the porous metal fiber mat allows reagents to contact the large active surface area. When the porous metal fiber mat is used as a catalyst carrier, it provides a large surface area impregnated / doped with a catalyst. The high porosity of the porous metal fiber mat allows reagents to contact the impregnated / doped surface.
[0074] In a sixth aspect, the present invention provides a use of the porous metal fiber mat according to the second aspect or the third aspect as a filter material. When the porous metal fiber mat is used as a filter material, a mixture of substances passes through the mat, wherein some elements of the mixture are prevented from passing through the mat, thereby separating the mixture.
[0075] All publications, issued patent documents, and patent applications cited herein are hereby incorporated by reference to the same extent as if each individual publication, issued patent document, or patent application was specifically and individually indicated to be incorporated by reference.
[0076] As used herein, the singular forms "a", "an", and "the" also include the plural forms, unless the context clearly dictates otherwise. Unless clearly stated otherwise, the use of the singular includes the plural. The terms "comprising", "containing", "including", and "having", as well as other forms (e.g., "include", "comprise", "contain", and "has") do not exclude the presence of other features. As used herein, whenever "comprising" is mentioned, it may also be interpreted as meaning "consisting essentially of" and "consisting of". For example, a slurry comprising particles selected from metal particles, metal oxide particles, or a combination thereof, and a polymer carrier in a solvent may also be considered to disclose that the slurry consists essentially of the components and the slurry consists of the components.
[0077] When the concentration units are expressed in degrees relative to their units, they can also be expressed as ratios. For example, the particle loading of a slurry is 0.2 g mL -1 Up to 0.9 g mL -1 The range can also be expressed as a range of 20 w / v% to 90 w / v%.
[0078] Aspects provided herein are also described in the following clauses:
[0079] 1. A method for preparing a porous metal fiber mat, the method comprising:
[0080] a. providing a slurry, the slurry comprising particles in a solvent and a polymer carrier, the particles being selected from metal particles, metal oxide particles or a combination thereof;
[0081] b. electrospinning the slurry to produce a composite fiber mat; and
[0082] c. Heating the composite fiber mat to produce a porous metal fiber mat.
[0083] 2. The method according to clause 1, wherein the particles are metal particles.
[0084] 3. The method according to clause 1, wherein the particles are metal oxide particles.
[0085] 3a. The method according to any of the preceding clauses, wherein the slurry comprises a sintering aid.
[0086] 3b. The method according to clause 3a, wherein the sintering aid is present in an amount of about 1 wt.% to about 15 wt.% based on the amount of metal particles, metal compound particles, or a combination thereof.
[0087] 3c. A method according to clause 3a or 3b, wherein the particles are aluminum particles and the sintering aid is selected from copper, tin, zinc, magnesium, KAlF 4 、AlCl 3 NH 4 Cl, LiCl or a mixture thereof.
[0088] 3d. A method according to clause 3c, wherein the sintering aid is magnesium or magnesium and KAlF 4 .
[0089] 3e. A method according to clause 3a or 3b, wherein the particles are titanium particles and the sintering aid is selected from iron, magnesium, copper, zinc, nickel, silicon or mixtures thereof.
[0090] 4. The method according to clause 1, wherein the particles are metal particles selected from the group consisting of nickel particles, copper particles, iron particles, aluminum particles, titanium particles, zinc particles, or mixtures thereof.
[0091] 4a. The method according to clause 4, wherein the metal particles are selected from aluminum particles, zinc particles or mixtures thereof.
[0092] 5. The method according to clause 1, wherein the particles are metal oxide particles selected from the group consisting of nickel oxide particles, copper oxide particles, iron oxide particles, aluminum oxide particles, titanium oxide particles, zinc oxide particles, or mixtures thereof.
[0093] 5a. The method according to clause 5, wherein the metal oxide particles are selected from nickel oxide particles, copper oxide particles, iron oxide particles, zinc oxide particles or mixtures thereof.
[0094] 5b. The method according to clause 5a, wherein the metal oxide particles are selected from nickel oxide particles, copper oxide particles or mixtures thereof.
[0095] 5c. The method according to clause 1, wherein the particles are selected from zinc particles, aluminum particles, nickel oxide particles, copper oxide particles, or mixtures thereof.
[0096] 6. A method according to any of the preceding clauses, wherein the particles have an average size of 0.01 μm to 2 μm, such as 0.1 μm to 2 μm, such as 0.2 μm to 0.8 μm.
[0097] 7. A method according to any of the preceding clauses, wherein the particle loading in the slurry is between 0.2 g mL -1 Up to 0.9 g mL -1 within the range.
[0098] 8. A method according to any of the preceding clauses, wherein the polymer carrier is polyacrylonitrile (PAN), polyethylene oxide (PEO), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polyamide (nylon), polymethyl methacrylate (PMMA), polyvinyl ether (PVE), polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), chitosan, lignin, cellulose or polylactic acid (PLA).
[0099] 9. A method according to any of the preceding clauses, wherein the polymer carrier is polyacrylonitrile (PAN), polyethylene oxide (PEO), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polyamide (nylon), polymethyl methacrylate (PMMA) or polyvinyl ether (PVE).
[0100] 10. The method according to any one of the preceding clauses, wherein the weight average molecular weight of the polymer carrier is 10 kgmol -1 Up to 1500 kg mol -1 .
[0101] 11. The method according to any of the preceding clauses, wherein the polymer carrier is selected from:
[0102] ·Weight average molecular weight is 50 kg mol -1 Up to 400 kg mol -1 PAN;
[0103] ·Weight average molecular weight is 15 kg mol -1 Up to 500 kg mol -1 or
[0104] ·Weight average molecular weight is 50 kg mol -1 Up to 1300 kg mol -1 PVP.
[0105] 12. The method according to any of the preceding clauses, wherein the polymer carrier is selected from:
[0106] PAN having a weight average molecular weight of 50 to 400 kg mol-1, such as 200 to 260 kg mol-1 (e.g., about 230 kg mol-1);
[0107] ·Weight average molecular weight is 15 kg mol -1 Up to 500 kg mol -1 (e.g. 15 kg mol -1 Up to 60 kg mol-1 (e.g., about 30 kg mol -1 )) of PEO, or a weight average molecular weight of 30 kg mol -1 Up to 90 kg mol -1 (e.g., about 60 kg mol -1 ) or PEO with a weight average molecular weight of 70 kg mol -1 Up to 130 kg mol -1 (e.g., about 100 kg mol -1 ) of a PEO; or
[0108] ·Weight average molecular weight is 50 kg mol -1 Up to 1300 kg mol -1 PVP.
[0109] 13. A method according to any of the preceding clauses, wherein the polymer carrier is selected from:
[0110] ·0.05 g mL -1 Up to 0.15 g mL -1 The amount provided in the slurry has a molecular weight of 200 kg mol -1 Up to 260 kg mol -1 PAN, optionally wherein the PAN has a molecular weight of about 230 kg mol -1 ;
[0111] ·0.08 g mL -1 Up to 0.20 g mL -1 The amount provided in the slurry has a molecular weight of 15 kg mol -1 Up to 60 kg mol -1 PEO, optionally wherein the molecular weight of the PEO is about 30 kg mol -1 ;
[0112] ·0.04 g mL -1 Up to 0.15 g mL -1 The amount provided in the slurry has a molecular weight of 30 kg mol -1 Up to 90 kg mol -1 PEO, optionally wherein the molecular weight of the PEO is about 60 kg mol -1 ;or
[0113] ·0.02 g mL -1 Up to 0.08 g mL -1 The amount provided in the slurry has a molecular weight of 70 kg mol -1Up to 130 kg mol -1 PEO, optionally wherein the molecular weight of the PEO is about 100 kg mol -1 .
[0114] 14. A method according to any of the preceding clauses, wherein the solvent is selected from water, dimethylformamide (DMF), ethanol, acetone, acetic acid, formic acid, chloroform, dichloromethane (DCM), dimethyl sulfoxide (DMSO), dimethylacetamide (DMA), toluene, oxolane or a mixture thereof.
[0115] 15. The method according to any of the preceding clauses, wherein the solvent is selected from water or dimethylformamide (DMF).
[0116] 16. The method according to any of the preceding clauses, wherein the slurry is prepared by mixing the solvent, the polymer vehicle and the particles at a temperature of at least 50°C.
[0117] 17. A method according to any one of the preceding clauses, wherein the slurry is prepared by mixing the solvent, the polymer vehicle and the particles at a temperature of 50°C to 80°C.
[0118] 18. A method according to any of the preceding clauses, wherein the slurry further comprises a surfactant, optionally wherein the surfactant is present in an amount of 0.001 g mL -1 Up to 0.05 g mL -1 The concentration exists in the range of
[0119] 19. The method according to clause 18, wherein the surfactant is selected from Triton X-100, oleic acid, cetyltrimethylammonium bromide, carboxymethylcellulose, or a combination thereof.
[0120] 20. A method according to any preceding clause, wherein the weight ratio of particles to polymer carrier in the slurry is at least 1:1, preferably 1:1 to 50:1, more preferably 1.5:1 to 15:1, even more preferably 1.5:1 to 9:1.
[0121] 21. The method according to any of the preceding clauses, wherein the electrospinning is performed with the slurry at a temperature of 18°C to 80°C.
[0122] 22. A method according to any of the preceding clauses, wherein the electrospinning is performed at a voltage of 5 kV to 25 kV.
[0123] 23. A method according to any one of the preceding clauses, wherein the electrospinning is carried out at 0.1 mL h -1To 10mLh -1 at a rate of .
[0124] 24. The method of any of the preceding clauses, wherein the electrospinning is performed using an electrospinning nozzle having a diameter of 15 to 25 gauge (0.51 mm to 1.83 mm).
[0125] 25. The method according to any of the preceding clauses, wherein the electrospinning is performed using a collecting plate located 2 cm to 30 cm from the electrospinning nozzle.
[0126] 26. A method according to any of the preceding clauses, wherein the electrospinning is performed using a plurality of electrospinning nozzles.
[0127] 27. The method according to any of the preceding clauses, wherein the electrospinning is performed at a relative humidity of no greater than 80%.
[0128] 28. The method according to any of the preceding clauses, wherein the composite fiber mat is heated to a temperature of 200°C to 2000°C (eg 400°C to 1200°C) during the heating step.
[0129] 29. A method according to any one of the preceding clauses, wherein during the heating step the temperature is set at 0.2°C min -1 to 2℃min -1 The rate at which the temperature increases.
[0130] 30. A method according to any of the preceding clauses, wherein the heating step is performed in a furnace.
[0131] 31. A method according to any of the preceding clauses, wherein the heating step is carried out in air.
[0132] 32. A method according to any one of the preceding clauses, wherein the composite fiber mat is exposed to H during the heating step. 2 Gas contact.
[0133] 33. A method according to any of the preceding clauses, wherein the composite mat is exposed during the heating step to a mixture containing at least 5 vol% H 2 of gas contact.
[0134] 34. A method according to any of the preceding clauses, wherein the composite mat is contacted with a 2 and N 2 Gas (e.g., 5 vol% H 2 / N 2 )touch.
[0135] 35. A method according to any of the preceding clauses, wherein the heating step is performed in two stages, optionally wherein both stages are performed in the same apparatus (eg, furnace).
[0136] 36. A method according to clause 35, wherein a first stage removes the polymer carrier in the composite fiber mat and sintering the particles, and a second stage reduces any metal compound particles to produce the porous metal fiber mat.
[0137] 37. The method according to clause 36, wherein the first stage is carried out under the conditions according to any one of clauses 28 to 34.
[0138] 38. A method according to clause 36 or clause 37, wherein the second stage is carried out under conditions according to any one of clauses 28 to 34.
[0139] 39. A method according to any of the preceding clauses, wherein prior to the heating step, the composite mat is folded onto itself, or a plurality of composite fiber mats prepared according to the method are stacked on top of each other.
[0140] 40. The method according to clause 39, wherein the folded or stacked composite fiber mat is subjected to a preheating step prior to said heating step and said reducing step.
[0141] 41. The method according to clause 40, wherein the preheating step is carried out at a temperature of 120°C to 400°C (e.g., about 250°C), optionally wherein the temperature is increased by 0.2°C min during the preheating step. -1 to 2℃min -1 The rate of increase.
[0142] 42. A porous metal fiber mat obtainable by a method according to any of the preceding clauses.
[0143] 43. A composite fiber mat obtainable by step a. and step b. according to any one of the preceding clauses.
[0144] 44. A porous metal fiber mat having:
[0145] At least 500cm -1 The specific surface area of
[0146] At least 0.05mm thickness.
[0147] 45. A porous metal fiber mat according to clause 44, wherein the porous metal fiber mat has a porosity of at least 50 vol%, such as at least 70 vol% or at least 80%, optionally 80 to 98 vol%, such as 80 to 90 vol%.
[0148] 46. A porous metal fiber mat according to clause 44 or clause 45, wherein the porous metal fiber mat has a specific surface area of 500 cm -1 Up to 50000cm -1 .
[0149] 47. A porous metal fiber mat according to any of clauses 44 to 46, wherein the porous metal fiber mat has an average pore size in the range of 0.5 μm to 5.0 μm, optionally wherein the average pore size is about 2.5 μm.
[0150] 48. A porous metal fiber mat according to any of clauses 44 to 47, wherein the porous metal fiber mat has a thickness in the range of 0.05 mm to 10 mm.
[0151] 49. A porous metal fiber mat according to any of clauses 44 to 48, wherein the metal fibers in the metal fiber mat are nickel fibers, copper fibers, iron fibers, aluminum fibers, titanium fibers or zinc fibers.
[0152] 50. A porous metal fiber mat according to any of clauses 44 to 49, wherein the metal fiber mat is obtainable by a method according to any of clauses 1 to 41.
[0153] 51. Use of a porous metal fiber mat according to any one of clauses 42 or 44 to 50 as an electrode.
[0154] 52. The use according to clause 51, wherein the electrode is used in a lithium sulfur battery, a redox flow battery, a supercapacitor or a fuel cell unit.
[0155] 53. Use of a porous metal fiber mat according to any one of clauses 42 or 44 to 50 as a catalyst or catalyst support.
[0156] 54. Use of a porous metal fiber mat according to any one of clauses 42 or 44 to 50 as a filter material.
[0157] The present invention will now be described by reference to the following examples. These examples should not be construed as limiting the present invention.
[0158] Example
[0159] Materials and methods
[0160] NiO powder was obtained from Fuel Cell Materials. CuO powder, PEO polymer, and DMF solvent were obtained from Sigma-Aldrich. Zn powder was obtained from American Elements. PAN polymer was obtained from Goodfellow. Unless otherwise noted, all materials were used as provided and without purification.
[0161] Particle size was measured using SEM images. 10 mg of particles were first dispersed in 1 mL of ethanol by sonication, and a drop of the dispersion was then dropped onto a carbon ribbon. The ribbon was placed in a scanning electron microscope. The magnification was adjusted to display >20 particles in the view.
[0162] After saving the image, use ImageJ to measure the diameters of 20 particles and calculate the average particle size.
[0163] Example 1: Preparation of a nickel pad of about 500 μm using polyacrylonitrile (PAN)
[0164] 0.8 g of polyacrylonitrile (PAN, 230 kg mol) was stirred at 70 °C using a magnetic stirrer. -1 ) was dissolved in 10 mL of dimethylformamide (DMF) to form a transparent PAN / DMF solution. 5 g of NiO (500 nm particle size) was gradually added to the solution under magnetic stirring. The slurry was stirred at 70 °C for 4 h to disperse the NiO particles evenly. After that, the slurry was transferred to a 10 mL syringe, after which the slurry was loaded onto the electrospinning machine. During the electrospinning process, the nozzle was placed 15 cm away from the roller collector; the temperature of the slurry was maintained at 50 °C; the syringe pumping rate was set to 1 mL h -1 ; The voltage applied to the nozzle was adjusted between 7-20 kV to ensure constant and stable extraction of the fibers.
[0165] The NiO / PAN fiber mat was placed on a zirconia tray and calcined in air at 1000 °C for 5 h to eliminate PAN and sinter NiO, with a temperature of 0.5 °C min -1 The heating rate was increased to 600 °C, and then increased to 2 °C min -1 The resulting NiO mat was then cut into a size that would fit in a tube furnace and heated to 1000°C in a tube furnace at 5% H 2 / N 2 The NiO mat was calcined in a molten-carbon atmosphere to reduce the NiO mat to the final product, i.e., a 500 μm thick Ni metal mat. The NiO mat was calcined at 800 °C for 5 hours at a rate of 2 °C min -1 The calcination was completed at a heating rate of .
[0166] Example 2: Preparation of a nickel pad of approximately 2 mm using PAN
[0167] The preparation steps and starting materials were the same as those used in Example 1 until the electrospinning step, after which two steps were added before calcination: the prepared NiO / PAN mat was folded twice; then it was pre-calcined in air at 250 °C for 2 h (at a rate of 1 °C min -1 The sample was heated at a rate of 20° and compacted with two stainless steel plates with a total weight of about 2 kg.
[0168] The pre-calcined mat was then subjected to the same calcination step as described in Example 1 to produce a 2 mm thick Ni metal mat.
[0169] Example 3: Preparation of a nickel pad of about 300 μm using polyethylene oxide (PEO)
[0170] 0.4 g polyethylene oxide (PEO, 100 kg mol -1 ) was dissolved in 10 mL of water at 70°C to form a transparent solution. Then 5 g of NiO (500 nm particle size) was gradually added to the solution under magnetic stirring. The slurry was electrospun under the same conditions as described in Example 1.
[0171] The as-spun NiO / PEO mat was cut and then heated in a tube furnace at 5% H 2 / N 2 The calcination was carried out at 800°C for 5 hours, with the temperature increasing to 400°C at a rate of 0.5°C min-1, and then the temperature increasing rate was increased to 2°C min-1 to reach 800°C.
[0172] Example 4: Preparation of a copper pad of about 500 μm using PAN
[0173] The same slurry preparation and electrospinning procedures as described in Example 1 were used, except that CuO powder (800 nm particle size) was used instead of NiO (500 nm particle size).
[0174] The as-spun CuO / PAN mat was calcined in air at 750 °C for 5 h with a heating rate of 0.5 °C min -1 The heating rate was increased to 600 °C and then to 2 °C min -1 , to reach 750 °C. The CuO mat was then cut and heated in a tube furnace at 5% H 2 / N 2 The samples were calcined at 650 °C for 5 h with a heating rate of 2 °C min -1 .
[0175] Example 5: Preparation of a copper pad of about 500 μm using PAN and a surfactant
[0176] The same slurry preparation and electrospinning procedures as those described in Example 1 were used, except that 5 g of CuO powder (200 nm particle size) was added to the PAN / DMF solution instead of NiO (500 nm particle size). 0.1 g of Triton X-100 was added to the slurry as a surfactant to improve particle dispersibility and reduce the viscosity of the slurry.
[0177] The as-spun CuO / PAN was subjected to the same calcination step as described in Example 4 to produce a Cu mat.
[0178] Example 6: Preparation of a zinc pad of approximately 300 μm using PEO and metallic zinc powder
[0179] 0.8 g polyethylene oxide (PEO, 60 kg mol -1 ) was dissolved in 10 mL DMF at 70°C to form a clear solution. 5 g of zinc (300 nm particle size) was then gradually added to the solution under magnetic stirring. The slurry was then electrospun using the same conditions as described in Example 1.
[0180] The as-spun Zn / PEO mat was cut and then heated in a tube furnace at 5% H 2 / N 2 The Zn metal pad was calcined in a molten-salt atmosphere to produce the final Zn metal pad product. The calcination was completed at 410 °C for 5 hours with a heating rate of 0.5 °C min -1 .
[0181] Example 7: Comparison of the properties of nickel fiber pad and nickel foam
[0182] Tensile strength and compression tests were performed on the nickel fiber mat and nickel foam samples (Ni-5763 obtained from RECEMAT BV) prepared as in Example 1. The specific surface area, density and porosity of the two materials are listed in the following table:
[0183]
[0184] Tension and compression tests are performed on Zwick / Roell universal testing platforms.
[0185] In the tensile test, the 400 μm thick samples were cut into 1.5 x 4 cm 2 The machine is designed to produce rectangular shapes and then loaded onto the machine. The machine is designed to produce rectangular shapes and then loaded onto the machine. -1 The sample is pulled at both ends at a rate of 1000 until the sample breaks. The tensile stress and strain are recorded.
[0186] In the compression test, the 400 μm thick sample was cut into 2 x 2 cm 2 The square shape is then placed on the machine. Then the equipment is used to cut the -1 The sample was compressed at a compression ratio of 100 until it reached 90% strain. The compressive stress and strain were recorded.
[0187] The tensile test results are shown in Figure 2 In the low strain / stress region, the curves for both the Ni pad and the Ni foam show linear behavior consistent with elastic deformation, where the deformation of the material is reversible after the load is withdrawn. The slope of this region is the Young's Modulus of the material. The Ni pad's curve is steeper, indicating its higher Young's Modulus and greater resistance to elastic deformation under tensile load.
[0188] After the linear region, both samples pass through a shoulder, which is the yield point. After this point, the deformation of the material is no longer reversible. The region after the yield point is nonlinear. The maximum stress corresponds to the ultimate tensile strength (UTS), after which the material breaks. Compared to Ni foam, the UTS of the Ni pad is higher and the resistance to fracture is better.
[0189] exist Figure 4 In the compression test of , Ni foam showed a shoulder at 0.23% strain, while Ni pad did not show this feature. This feature is the transition point from elastic deformation to plastic deformation, after which the deformation is irreversible. This indicates that Ni pad is less resistant to elastic deformation under compressive load than Ni foam, and most of its deformation under compression is irreversible.
[0190] Example 8 - Observation of the electrochemical properties of nickel fiber mat and nickel foam
[0191] The tests were conducted using the same types of nickel fiber mats and nickel foams as used in Example 7, except that the thickness of the mat / foam was varied as indicated below. Prior to electrochemical testing, the nickel fiber mats and nickel foams were prepared by 2 S 2 The samples were sulfided by boiling in 1M NaOH solution for 1 hour, which converted the surface nickel into nickel sulfide. The sulfided nickel pads were tested in two electrochemical applications:
[0192] The first test was as an electrochemical catalyst for polysulfide oxidation / reduction reactions: a 1.5 mm sulfurized nickel fiber mat was placed as the working electrode of a three-electrode cell with a platinum wire as the counter electrode and Ag / AgCl as the reference electrode. 2 S 2The nickel fiber mat was tested by linear sweep voltammetry (LSV) in +1M NaOH solution. The nickel fiber mat showed an activity 4-5 times that of 2 mm nickel foam tested under the same conditions (e.g. Figure 5 ).
[0193] The second test was as a cathode for a lithium-ion battery: a 500 μm sulfurized nickel fiber mat was assembled into a standard CR2032 coin cell as the cathode, with a lithium chip as the anode. The coin cell was operated at 2 mA cm -2 Cycling between 1.2 V and 2.7 V at current densities of >20 mAh cm -2 Area capacity (such as Figure 6 The areal capacity compares favorably with that of commercial lithium-ion batteries, which are typically less than 5 mAh cm -2 .
[0194] Example 9: Preparation of aluminum pad using polyethylene oxide (PEO) and sintering aid
[0195] 0.7 g polyethylene oxide (PEO, 60 kg mol -1 ) was dissolved in 10 mL of dimethylformamide (DMF) at 70°C to form a transparent PEO / DMF solution. 2 g of aluminum (300-500 nm particle size), 0.3 g of KAlF 4 Gradually add to the solution under magnetic stirring. The slurry is then electrospun using the same conditions as described in Example 1.
[0196] The as-spun composite mat was cut and then heated in a tube furnace at 5% H 2 / N 2 Calcination in atmosphere to produce the final aluminum fiber metal mat product. 4 Decomposed during the process. Calcination was completed at 600 °C in 5 hours with a heating rate of 0.5 °C min -1 .
[0197] Example 10: Preparation of aluminum / magnesium pad using polyethylene oxide (PEO) and sintering aid
[0198] 0.7 g polyethylene oxide (PEO, 60 kg mol -1 ) was dissolved in 10 mL of dimethylformamide (DMF) at 70°C to form a transparent solution. 2 g of aluminum (300 nm particle size), 0.1 g of magnesium, 0.2 g of KAlF 4 Gradually add to the solution under magnetic stirring. The slurry is then electrospun using the same conditions as described in Example 1.
[0199] The as-spun composite mat was cut and then heated in a tube furnace at 5% H 2 / N 2 Calcination in atmosphere to produce the final Al / Mg alloy fiber metal mat product. 4 Decomposed during the process. Calcination was completed at 600 °C in 5 hours with a heating rate of 0.5 °C min -1 .
[0200] Example 11 - Observation of the electrochemical properties of nickel fiber mat and nickel foam as two electrodes in an alkaline water electrolyzer
[0201] The test was conducted using the same kind of nickel fiber mat and nickel foam as used in Example 7. The test was conducted using an H-Cell containing 100 mL of 1M KOH aqueous solution. The nickel fiber mat or nickel foam was used as both the cathode (hydrogen electrode) and anode (oxygen electrode) of the electrolyzer.
[0202] Apply 10mAcm -2 、50mAcm -2 、100mAcm -2 、200mAcm -2 and 500mAcm -2 The current density was passed through the electrode for 5 minutes. The average voltage was recorded and the voltage is shown in Figure 6 No catalyst was coated on the nickel fiber mat or nickel foam tested. The results are shown in Figure 6 In the figure, it can be seen that the nickel fiber mat prepared according to the present invention provides a lower voltage than the nickel foam. The lower the voltage, the better the performance.
Claims
1. A method for preparing a porous metal fiber mat, the method comprising: a. providing a slurry, the slurry comprising particles in a solvent and a polymer carrier, the particles being selected from metal particles, metal compound particles or a combination thereof; b. electrospinning the slurry to produce a composite fiber mat; as well as c. Heating the composite fiber mat to produce a porous metal fiber mat. 2 . The method according to claim 1 , wherein the particles are metal particles selected from the group consisting of nickel particles, copper particles, iron particles, aluminum particles, titanium particles, zinc particles, or mixtures thereof. 3 . The method according to claim 1 , wherein the particles are metal compound particles selected from the group consisting of nickel oxide particles, copper oxide particles, iron oxide particles, aluminum oxide particles, titanium oxide particles, zinc oxide particles, or mixtures thereof.
4. The method according to any one of the preceding claims, wherein the average size of the particles is from 0.01 μm to 2 μm.
5. The method according to any one of the preceding claims, wherein the particle loading in the slurry is between 0.2 g mL -1 Up to 0.9 g mL -1 within the range.
6. The method according to any of the preceding claims, wherein the polymer carrier is polyacrylonitrile (PAN), polyethylene oxide (PEO), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polyamide (nylon), polymethyl methacrylate (PMMA), polyvinyl ether (PVE), polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), chitosan, lignin, cellulose or polylactic acid (PLA).
7. The method according to any one of the preceding claims, wherein the polymer carrier is selected from: ·Weight average molecular weight is 50 kg mol -1 Up to 400 kg mol -1 PAN; ·Weight average molecular weight is 15 kg mol -1 Up to 500 kg mol -1 or ·Weight average molecular weight is 50 kg mol -1 Up to 1300 kg mol -1 PVP.
8. The method according to any one of claims 1 to 6, wherein the polymer carrier is selected from: ·0.05 g mL -1 Up to 0.15 g mL -1 The amount provided in the slurry has a molecular weight of 200 kg mol -1 Up to 260 kg mol -1 PAN, optionally wherein the PAN has a molecular weight of about 230 kg mol -1 ; ·0.08 g mL -1 Up to 0.20 g mL -1 The amount provided in the slurry has a molecular weight of 15 kg mol -1 to 60k gmol -1 PEO, optionally wherein the molecular weight of the PEO is about 30 kg mol -1 ; ·0.04 g mL -1 Up to 0.15 g mL -1 The amount provided in the slurry has a molecular weight of 30 kg mol -1 to 90k gmol -1 PEO, optionally wherein the molecular weight of the PEO is about 60 kg mol -1 ;or ·0.02 g mL -1 Up to 0.08 g mL -1 The amount provided in the slurry has a molecular weight of 70 kg mol -1 to 130k gmol -1 PEO, optionally wherein the molecular weight of the PEO is about 100 kg mol -1 .
9. The method according to any one of the preceding claims, wherein the solvent is selected from water, dimethylformamide (DMF), ethanol, acetone, acetic acid, formic acid, chloroform, dichloromethane (DCM), dimethyl sulfoxide (DMSO), dimethylacetamide (DMA), toluene, oxolane or mixtures thereof.
10. The method according to any one of the preceding claims, wherein the slurry further comprises a surfactant, optionally wherein the surfactant is present in an amount of 0.001 g mL -1 Up to 0.05 g mL -1 The concentration exists in the range of 11. The method according to any one of the preceding claims, wherein the composite fiber mat is heated to a temperature of 200°C to 2000°C during the heating step.
12. The method according to any one of the preceding claims, wherein during the heating step the temperature is set at 0.2°C min -1 to 2℃min -1 The rate at which the temperature increases.
13. The method according to any one of the preceding claims, wherein the composite fiber mat is contacted with H2 gas during the heating step, optionally wherein the H2 gas comprises at least 5 vol% H2.
14. A method according to any one of the preceding claims, wherein the heating step comprises a first stage for removing the polymer carrier in the composite fiber mat and sintering the particles and a second stage for reducing any metal compound particles to produce the porous metal fiber mat.
15. The method according to any one of the preceding claims, wherein before the heating step, the composite mat is folded onto itself, or a plurality of composite fiber mats produced according to the method are stacked on top of each other, optionally wherein the folded or stacked composite fiber mats are subjected to a preheating step before the heating step and the reducing step.
16. A porous metal fiber mat obtainable by a method according to any one of the preceding claims.
17. A porous metal fiber mat, comprising: At least 500cm -1 The specific surface area of At least 0.05mm thickness.
18. The porous metal fiber mat according to claim 17, wherein the porous metal fiber mat has a porosity of at least 50 vol%, such as from 80 vol% to 98 vol%, or such as from 80 vol% to 90 vol%.
19. The porous metal fiber mat according to claim 17 or claim 18, wherein the porous metal fiber mat has a specific surface area of 500 cm -1 Up to 50000cm -1 .
20. The porous metal fiber mat according to any one of claims 17 to 19, wherein the average pore size of the porous metal fiber mat is in the range of 0.5 μm to 5.0 μm, optionally wherein the average pore size is about 2.5 μm.
21. The porous metal fiber mat according to any one of claims 17 to 20, wherein the porous metal fiber mat has a thickness in the range of 0.05 mm to 10 mm.
22. The porous metal fiber mat according to any one of claims 17 to 21, wherein the metal fibers in the metal fiber mat are nickel fibers, copper fibers, iron fibers, aluminum fibers, titanium fibers or zinc fibers.
23. The porous metal fiber mat according to any one of claims 17 to 21, wherein the metal fiber mat is obtainable by a method according to any one of claims 1 to 15.
24. Use of a porous metal fiber mat according to any one of claims 16 to 23 as an electrode, optionally in a lithium sulfur battery, a redox flow battery, a supercapacitor or a fuel cell unit.
25. Use of the porous metal fiber mat according to any one of claims 16 to 23 as a catalyst or catalyst support, or as a filter material.
Citation Information
Patent Citations
Method for preparing foam metal through freeze drawing technology
CN107552797A
Rechargeable Lithium-Ion Battery with Metal-Foam Anode and Cathode
US20210344017A1